Creating entrepreneurial education programs and ecosystems in universities. (19th June 2019) - Závodská, Anna; Šramová, Veronika; Liberona, Dario
Research has shown that majority of start-ups fail (Patel, 2015; Shorewala and Chaudhary, 2016; Silas, 2004) due to following reasons: premature scaling, poor product, ignoring customer needs, etc. One of the main factors is caused by the lack of entrepreneurial skills of founders and their co-workers. Creating favourable start-up ecosystem requires cooperation of many stakeholders including enthusiastic individuals. Universities play a crucial role in the ecosystem creation. They are actively trying to prepare students for their entrepreneurial career by organising events as well as offering courses. This paper describes the development of an entrepreneurial ecosystem at the University of Žilina in Slovakia and at Santa María Technical University in Chile. The case study method was used for describing experiences with the creation of an entrepreneurial ecosystem. Authors have tested various approaches in order to develop a complex entrepreneurial ecosystem. Proposed system and methodologies serves as a basis for future research.